Lily and Dunkin - Gephart, Donna (Delacorte Press, 2016)
"Lily Jo McGrother, born Timothy McGrother, is a girl. But being a girl is not so easy when you look like a boy. Especially when you're in the eighth-grade. Norbert Dorfman, nicknamed Dunkin Dorfman, is bipolar and has just moved from the New Jersey town he's called home for the past thirteen years. This would be hard enough, but the fact that he is also hiding from a painful secret makes it even worse. One summer morning, Lily Jo McGrother meets Dunkin Dorfman, and their lives forever change"--